2018
DOI: 10.1002/jcp.27248
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of long noncoding RNA MEG3 inhibits the osteogenic differentiation of periodontal ligament cells

Abstract: Upregulation of MEG3 inhibits the osteogenic differentiation of periodontal ligament cells by downregulating BMP2 expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 38 publications
1
27
0
Order By: Relevance
“…Studies in past several years also showed that the development of periodontitis is also accompanied by changed in expression patterns of a large set of lncRNAs [11]. Certain lncRNA, such ANCR and MEG3 regulate osteogenic differentiation to participate in the pathogenesis of periodontitis [12, 13]. LncRNA PTCSC3 has been characterized as a tumor suppressor [14], while its roles in other human diseases are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in past several years also showed that the development of periodontitis is also accompanied by changed in expression patterns of a large set of lncRNAs [11]. Certain lncRNA, such ANCR and MEG3 regulate osteogenic differentiation to participate in the pathogenesis of periodontitis [12, 13]. LncRNA PTCSC3 has been characterized as a tumor suppressor [14], while its roles in other human diseases are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that MEG3 can compete with BMP2 mRNA for interaction with hnRNPI. Therefore, MEG3 overexpression suppresses BMP2 levels and attenuates osteogenic differentiation in periodontal ligament cells (11).…”
Section: Roles Of Lncrna Meg3 In Osteogenic Differentiationmentioning
confidence: 99%
“…BMP2 is an important molecule responsible for regulation of osteogenesis (18). Modifications of BMP2 mRNA are associated with heterogeneous nuclear ribonucleoprotein I (hnRNPI), and the downregulation of hnRNPI can in turn decrease BMP2 protein expression levels (11). It has been shown that MEG3 can compete with BMP2 mRNA for interaction with hnRNPI.…”
Section: Roles Of Lncrna Meg3 In Osteogenic Differentiationmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang and colleagues reported that lncRNA‐POIR expression was significantly up‐regulated in periodontitis tissues, and its abnormal expression was correlated with the osteogenesis of PDLCs mediated by NF‐kappa B/Wnt pathway, suggesting that lncRNA‐POIR may be an important molecular target in periodontitis 10 . Recently, Liu et al 11 indicated that overexpression of MEG3 inhibited cell viability, osteogenic differentiation, and increased cell apoptosis of periodontal ligament cells by down‐regulating BMP2 expression. To explore potential lncRNAs involved in the development of periodontitis, the lncRNA microarray profiles of gingival tissue from periodontitis patients and healthy controls were analyzed, and several differentially expressed lncRNAs were identified, such as lncRNA‐01126, KLLP, and FIFH.…”
Section: Introductionmentioning
confidence: 99%